Diagnostic criteria and classification of hydromorphic soils in forest-steppe zone of the Oka-Don Lowland - M. A. Smirnova; N. I. Lozbenev (Бюллетень Почвенного института им. В.В. Докучаева)
The soil cover of the Oka-Don Lowland interfluves differs significantly in its component composition from the soil cover of the Central Russian Upland, despite being formed under similar climatic conditions. The soils of the Oka-Don Lowland are complex in terms of their genesis, which causes difficulties in diagnosing and classifying them. The paper presents the results of field testing of non-drained soils of the Oka-Don Lowland area, as well as their diagnostics according to the three most widely used soil classifications in Russia: system of USSR (1977), system of Russia (2004) and international WRB, a regional correlation of classifications is performed. It is shown that the soil cover is represented by contrasting combinations of soils with a thick humus horizon underlain by a non-carbonate / carbonate / very waterlogged horizon, solonetz, solonetzic, solodized, bog soils, and soils with a light eluvial horizon; as a rule, in the middle and lower parts of the profile; all soil profiles contain traces of waterlogging. The absence of clear diagnostic criteria based on soil properties, the absence of natural vegetation and data on the average long-term level of soil and groundwater makes soil diagnostics according to the USSR soil classification highly dependent on the qualifications of the soil scientist-researcher. The high degree of formalization of substantive classifications (soil classification of Russia and WRB) leads to the fact that genetically close soils can belong to different taxonomic groups at a high level (soil types in the classification of Russia, main qualifiers according to WRB). The assessment of pedodiversity can differ greatly depending on the classification system used.